IS THERE A RELATIONSHIP BETWEEN PAIN, LIMITS OF STABILITY AND SENSORY INTERACTION BALANCE IN PATIENTS WITH LUMBAR DISC HERNIATION? A CROSS-SECTIONAL STUDY - Melda SOYSAL TOMRUK; Alp Tunca YAPIC (Rojan GÜMÜŞ, 2021)
: Lumbar Disc Herniation (LDH) is a disorder causing pain and somatosensory loss. Although the association between pain and postural control in chronic low back pain is known, the relationship between pain and sensory problems with postural control is unknown in LDH, which is one of the most serious conditions among diseases. The purpose of the study was to determine the relationship between pain severity, limits of stability, and sensory interaction balance in patients with LDH. A total of 119 LDH patients, 64 of whom were women and 55 were men, were included in this cross-sectional study. Pain severity and postural control of the patients were measured by using the Visual Analog Scale and Biodex Balance Device, respectively. Limits of Stability and Clinical Test of Sensory Interaction Balance tests were used for postural control evaluation. The results of our study indicated that pain and disability were positively correlated with sensory interaction balance (p<0.05) while there was no statistically significant correlation between pain, disability, and limits of stability (p>0.05). In patients with LDH, the sensory interaction balance was negatively affected by the increased pain and disability level, while LOS was not. Therefore, in addition to reducing pain and disability, approaches to increase the sensory interaction balance should be adopted in physiotherapy programs for these patients.